Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Pelanggan J&T Express Pada Masa Pandemi COVID-19 - Puji Isyanto; Kartika Wijayanti (Politeknik Ganesha Medan, 2022)
This study aims to determine, explain, and analyze service quality and brand image on customer satisfaction, the correlation of service quality and brand image on customer satisfaction, the effect of service quality and brand image partially on customer satisfaction, the effect of service quality and brand image simultaneously on customer satisfaction. customer satisfaction. This type of research is quantitative with descriptive and verification research methods.. The sampling technique uses a non-probability sampling technique, namely purposive sampling. Data collection techniques using questionnaires and to analyze data using scale range and path analysis. The results showed that the service quality of J&T Express COVID-19 was quite good because it was in the criteria range of the scale quite agree, the J&T Express brand image perceived was considered good because it was in the criteria range. agree scale, J&T Express customer satisfaction felt is considered good because it is in the agreed scale criteria range, there is a correlation between service quality and brand image with a very strong and unidirectional correlation level because the results positive correlation coefficient, there is a partial influence between service quality and brand image on customer satisfaction, there is a simultaneous influence between service quality and brand image on customer satisfaction..